Introduction [In Pulses for nutrition in India: Changing patterns from farm to fork] - Roy, Devesh; Joshi, Pramod Kumar; Chandra, Raj (International Food Policy Research Institute, 2017)
The remainder of this chapter presents some facts that form the background motivation for this book: the production and consumption patterns of India’s pulse sector, the global context of trade in pulses and the position of India therein, the nutritional and environmental characteristics that make pulses a salient crop in meeting human needs, and the different initiatives for the pulses sector taken up by the government of India.